2000
DOI: 10.1109/23.903784
|View full text |Cite
|
Sign up to set email alerts
|

Predicting error rate for microprocessor-based digital architectures through C.E.U. (Code Emulating Upsets) injection

Abstract: --This paper investigates an approach to study the effects of upsets on the operation of microprocessorbased digital architectures. The method is based on the injection of bitf lips, randomly in time and location by using the capabilities of typical application boards. Experimental results, obtained on programs running on two different digital boards, built around an 80C51 microcontroller and a 320C50 Digital Signal Processor, illustrate the potentialities of this new strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(33 citation statements)
references
References 10 publications
0
30
0
2
Order By: Relevance
“…Aunque, el tiempo necesario para inyectar el fallo es relativamente corto, estos métodos son muy intrusivos ya que requieren la modificación del código original. En [15] Velazco et al describen una técnica software basada en rutinas de interrupción de servicio denominada CEU (Code Emulated Upset) para inyección de fallos. La implementación del método se realiza sobre una arquitectura hardware, denominada THESIC (Testbed for Harsh Environment Studies on Integrated Circuits), es una plataforma genérica que se encarga de generar las interrupciones que activan la inyección, las localizaciones del fallo, y de leer los resultados.…”
Section: Trabajos Previosunclassified
“…Aunque, el tiempo necesario para inyectar el fallo es relativamente corto, estos métodos son muy intrusivos ya que requieren la modificación del código original. En [15] Velazco et al describen una técnica software basada en rutinas de interrupción de servicio denominada CEU (Code Emulated Upset) para inyección de fallos. La implementación del método se realiza sobre una arquitectura hardware, denominada THESIC (Testbed for Harsh Environment Studies on Integrated Circuits), es una plataforma genérica que se encarga de generar las interrupciones que activan la inyección, las localizaciones del fallo, y de leer los resultados.…”
Section: Trabajos Previosunclassified
“…In [3] we proposed an initial estimation of τ obtained by using two fault injection methods that considered as targets of injection all the Special Function Registers of the microcontroller and the 128 bytes internal memory registers. The first considered method injects faults by executing suitable pieces of code and is called CEU (Code Emulating an Upset) technique [5] [6] the second method instead uses an HDL model of the device [7], for which code modifications are implemented in order to virtually change run-time every part composing the device. The two models were in accordance ( Table 1) and showed that the sensitivity to bit flips resulted strongly related to the executed program.…”
Section: Seu Effects On Program Execution Flowmentioning
confidence: 99%
“…Las primeras aproximaciones se presentan en [Velazco et al 1990y Martinet 1992. El láser se utiliza para cortar pistas internas y conexiones metalizadas de los circuitos integrados, generando fallos permanentes.…”
Section: Inyección Mediante Radiación Láserunclassified